German government invests EUR15 million in major new program to pay small-scale farmers to produce ecosystem services, including climate change adaptation and mitigation - Wollenberg, Eva Karoline (2023)
The International Group of Seven (G7) Presidency (Germany) used an analysis of payments for ecosystem services and innovative finance to develop the CompensAction Initiative to incentivize small-scale farmers to produce ecosystem services. As a first action, in 2022 the German Federal Ministry of Economic Cooperation and Development (BMZ) invested EUR 15 million in three projects of the International Fund for Agricultural Development (IFAD). BMZ will continue to invest at least $1-2 million/year in CompensAction projects.